DETERMINING THE INFLUENCE ON THE QUALITY INDICATOR OF COTTON FIBER DURING THE CLEANING PROCESS OF COTTON RAW MATERIALS IN A UHK INSTALLATION - Kozokov Saidmukhtar Olimjon ugli; Egamov Sokhibjon Olimdzhanovich; Muradov Rustam Muradovich (International Journal of Innovations in Engineering Research and Technology, 2024)
In this article, we have studied to what extent cotton fiber affects quality indicators in the process of cleaning cotton at the UHK unit with large impurities. At the same time, tables and graphs were formed on the UHK unit to what extent they affect the quality indicators and the fiber quality indicators of these samples were identified in the HVI system, taken for a sample after cleaning raw cotton.